Property development of hydroxyapatite ceramics by two-step sintering - Panyata S. (2014)
In this research, the two-step sintering method was employed to develop the physical properties of Hydroxyapatite (HA) ceramics. HA powder was extracted from bovine bone and vibro-milling method was used to make the fine particles. For the two-step sintering process, the samples were heated up to the first step temperature (T 1=1200°C) for 6 min then the temperature was lowered down to second step temperatures (T 2=1150°C and 1100°C) for 5, 10 and 15 h. Another set of samples were heated up to the first step temperature (T 1=1250°C) for 6 min then the temperature was lowered down to second step temperature (T 2=1150°C) for 5, 10 and 15 h. X-ray diffraction (XRD) was carried out for investigating the phase formation in the prepared ceramics. Physical properties of the prepared ceramics were studied such as porosity, density by Archimedes's principle. It is found that most of the samples exhibit Ca 5(PO 4) 3(OH) phase with JCPDS number 09-0432. The first step temperature plays the most roles on controlling the density of HA ceramics than T 2 and dwell times. Microstructures of the HA powder and ceramics were characterized using scanning electron microscope (SEM). The feasibility in using the prepared ceramics for bone replacement applications was discussed. © (2012) Trans Tech Publications.